Effect of Soil Amendment with Neem Seed Cake on Tomato Plant Growth and Development, Fruit Quality and Storability - Aghofack Nguemezi, Jean; Doumdi Roger, Braogue (Journal of Science and Technology, 2020)
In Cameroon, most of tomatoes (Solanum lycopersicum) are produced in the Western Highlands. During the period of production peaks farmers are faced with enormous postharvest losses. Furthermore, necessary great quantities of chemical inputs are some of potential threats to fruits quality and the environment. Since events occurring in the field finally impact the quality and storability of agricultural produces, the present study aimed at improving these parameters through soil amendment with neem seed cake (NSC) as bioeffector while preserving the environment. The NSC was therefore used at four doses (0 g, 4 g, 8 g and 12 g per plant). The experiment was carried out in a complete randomized block design with six repetitions in each treatment. Treatments began at the 2nd week after seedling transplantation and were continued at three weeks intervals. The plant growth and development, fruit quality and storability parameters were determined. The plant height, stem diameter, number of leaves per plant, number of branches per plant, time elapsed between the seedling transplanting date and the date of the appearance of the first flower, number of flower buds per plant, number of flowers per plant, number of grapes per plant, number of fruits per plant, fruit physiological weight loss (PWL), fruit titratable acidity (TA) and fruit senescence rate were positively influenced by the soil application of NSC, the dose of 12g/plant having been the most efficacious. The increase in TA was an indication of an improvement of the quality whereas the reduction of the PWL and the decrease in the rate of senescence were in favor of a better postharvest conservation of tomato fruits as results of soil amendment with NSC.